MUSICAL TEACHING IN EARLY CHILDHOOD TEACHER TRAINING - Zilli, Lía Rosa (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
The present work exposes and socializes some possible dimensions to be approached from Musical Education in the training of Initial Education teachers. The discussion and reflection on various experiential instances in higher education are structured around the development of musical and fictional games, concordant stimuli, a multimodal approach to musical works and some contributions from pedagogy that discuss the notion of destiny - which refers to a loss of singularity that perches on childhoods- when it comes to thinking about educational policies and their formation. From there, this work establishes a plurality of possibilities that, located from musical education, can be offered to those who work together with them. Some dimensions of analysis are proposed that, based on communicative musicality, the approach of early musical cognition and the theory of embodied cognition, make possible in musical practices with children: listening, enjoyment, experimentation and production- contextualization of different artistic manifestations in Initial Education.